Peran Guru PAI dalam Mengembangkan Kecerrdasan Emosional dan Spiritual Siswa di MI Ittaqu Surabaya - Dewi Pertamasari (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This research is motivated by the continued presence of students who are unable to control their emotions, are easily offended, lack self-confidence, and are less active in worship and religious activities at school. These conditions indicate the importance of the role of Islamic Religious Education teachers in fostering students' emotional and spiritual intelligence as part of character formation. This study aims to determine the role of Islamic Religious Education teachers in developing students' emotional and spiritual intelligence at MI ITTAQU Surabaya. The study used a qualitative descriptive approach with field research. Data collection techniques were carried out through observation, interviews, and documentation. Data were analyzed using the Miles and Huberman interactive model which includes data reduction, data presentation, and drawing conclusions. The results show that Islamic Religious Education teachers play a significant role in shaping students' emotional and spiritual intelligence through habituation of worship, role models, religious guidance, and a personal approach. These efforts have an impact on increasing student discipline in worship, the ability to control emotions, as well as an attitude of responsibility and mutual respect in everyday life.